Laboratory differentiation of Cushing's syndrome - Reimondo, Giuseppe; Pia, Anna; Bovio, Silvia; Allasino, Barbara; Daffara, Fulvia; Paccotti, Piero; Borretta, Giorgio; Angeli, Alberto; Terzolo, Massimo (Clinica chimica acta, 2008)
Cushing's syndrome (CS) is a complex of signs and symptoms due to chronic glucocorticoid excess from a variety of causes. Although CS is considered a rare disease, recent studies have suggested that it may be more frequent than previously expected in various clinical settings (i.e. subjects suffering from diabetes, osteoporosis or metabolic syndrome). If confirmed in large population-based studies, more widespread screening for CS may be warranted. Missed diagnosis of CS may have detrimental consequences because hypercortisolism, even if not clinically apparent, increases the probability of future cardiovascular events through induction/amplification of several risk factors (hypertension, central adiposity, thrombophilic state, etc.). Identifying CS has represented one of the most challenging problems for the clinical endocrinologist since no test is 100% sensitive and specific. This review article will be focus on diagnostic laboratory procedures that support a rationale approach in the screening evaluation and in the differential diagnosis of the endogenous CS. Notwithstanding the difficulties derived from laboratory reliability and the adoption of a hormonal cut-off close to the sensitivity of many commercially available assays, an increasing amount of data have provided novel information aimed to meet the demand of inexpensive, convenient and reliable laboratory procedures.